Methodology to evaluate transversal competences in the master's degree in industrial engineering based on a system of rubrics and indicators - Carlos Llopis-Albert; Francisco Rubio (Multidisciplinary Journal for Education, Social and Technological Sciences)
This paper presents a methodology to evaluate transversal competences in the context of the subject “Design and application of industrial equipment” in the Master's Degree in Industrial Engineering at Universitat Politècnica de València (Spain). The competency-based education implies several activities, such as a project-based learning that must be eventually defended in public by students in groups. Evidence of learning is collected based on a well-defined system of rubrics and indicators, which are known in advance by students. We have observed that the use of such techniques improves the students learning on the contents of the subject, allows to acquire the transversal competences related to the analysis and problem solving, and enhances the ability to understand concepts intuitively. Moreover, results clearly show a positive influence on the use of such tools for improving the professional and ethical commitment to the issues raised.